PENGARUH KONSENTRASI PUPUK ORGANIK CAIR (POC) KULIT BAWANG MERAH TERHADAP PERTUMBUHAN TANAMAN KEMBANG KOL (Brassica oleracea var. botrytis) - HIDAYAH, NUR; RAKIAN, TRESJIA CORINA; AFA, LA ODE (Jurnal Agroteknos, 2022)
Cauliflower is a vegetable plant of the Brassicaceae family that has high economic value. Increased production requires the right input of cultivation technology. Shallot skin can be used as a liquid organic fertilizer that can increase plant growth. The purpose of the research is to determine the effect of concentrations of liquid organic fertilizer on shallot skin on the growth of cauliflower. This research was conducted from December 2021 to February 2022, at the research area of Agriculture Faculty, Halu Oleo University, Kendari. The research design used was a randomized block design with fourth treatments, concentrations of liquid organic fertilizer i.e. P0 = without liquid organic fertilizer (control), P1 = 20 ml L-1, P2 = 40 ml L-1, P3 = 60 ml L-1. The analysis of data on plant height, leaf number, and dry weight of plant, using ANOVA, if the analysis results are significant (Fhit> Ftab) then continue with DMRT test on α=0.05. The results showed that the concentrations of liquid organic fertilizer on shallot skin significance on plant height, leaf number, and dry weight of plant. The concentration of liquid organic fertilizer on shallot skin, 40 ml L-1 can improve the plant growth of cauliflower.